Effect of Leadership Styles on Employee Productivity in Nepalese Commercial Banks - Khanal, Badrinath (Dibyajyoti Journal, 2024)
Different leadership styles can significantly affect organizational outcomes and employee well-being. There are many distinct leadership philosophies, and a leader may choose to implement a certain style depending on their inclinations, the circumstances, and the demands of their group. The aim of this study was to investigate the impact of different leadership styles on employee productivity in the banking sector. The study employed a descriptive and causal comparative research design. This quantitative research aimed to establish the relationships between dependent and independent variables. The population consisted of employees from Nepalese commercial banks, with 384 complete responses gathered through a judgmental sampling method from initial 390 questionnaires distributed. The findings shows the transformational leadership, transactional leadership, charismatic leadership and laissez-faire leadership are all positive and statistically significant on the employee productivity. The consistency in the positive effects of transformational charismatic leadership and laissez-faire leadership across different contexts suggests that these styles may be universally beneficial, although the degree of impact may vary depending on the organizational environment and culture. Transactional leadership, while effective, may need to be complemented with other styles, especially transformational and charismatic, to achieve optimal outcomes.